The Cultural Image of the Monarch in Jordan - Małachowski, Grzegorz (Załącznik Kulturoznawczy, 2022)
King of France, Luis IV said “I am the state”. The rulers of Jordan could repeat that phrase because their country is unique. It is one of a few states holding the name of the ruling family. Like the neighboring Kingdom of Saudi Arabia, Jordan was created by members of a family after which the country is named. The Hashemite Kingdom of Jordan – this is its full name, was created and ruled by the Hashemites, direct descendants of the Prophet Muhammad. Monarchs from the Hashemite dynasty have left a distinct mark on the state and people living in it. They adopted certain elements of the local culture and carved a unified, albeit somewhat artificial version out of them. Who are they? How did they achieve it? How are they presented? What is Jordanian culture? And finally, what is the cultural image of monarch of Jordan? These are the questions that the author will try to answer in this paper.